“คติชนสร้างสรรค์”: บทปริทัศน์บริบททางสังคมและแนวคิดที่เกี่ยวข้อง - ณ ถลาง ศิราพร (Journal of Letters, 2016)
ทุกวันนี้ วัฒนธรรมโดยเฉพาะคติชนมีความเปลี่ยนแปลงอย่างรวดเร็วซึ่งไม่ใช่เป็นความเปลี่ยนแปลงตามปกติธรรมดาของวัฒนธรรม แต่เป็นความเปลี่ยนแปลงอันมีปัจจัยทางสังคมเป็นตัวเร่งและเป็นตัวกำหนด ทำให้เกิดการสร้างสรรค์คติชนในรูปแบบและเนื้อหาใหม่ๆ หลายลักษณะ โครงการ “คติชนสร้างสรรค์ฯ”: พลวัตและการนำคติชนไปใช้ในสังคมไทยร่วมสมัย เป็นโครงการวิจัยที่พยายามอธิบายปรากฏการณ์พลวัตของคติชนในลักษณะต่างๆ ในบริบททางสังคมไทยในปัจจุบัน บทความนี้ปริทัศน์บริบททางสังคม สรุปแนวคิด และยกตัวอย่างวิทยานิพนธ์ที่เกี่ยวข้องกับปรากฏการณ์ “คติชนสร้างสรรค์” บทความนี้นำเสนอว่าบริบททางสังคมที่เกี่ยวข้องกับปรากฏการณ์ “คติชนสร้างสรรค์” ได้แก่ บริบทสังคมโลกาภิวัตน์และการท่องเที่ยว บริบททุนนิยมและเศรษฐกิจสร้างสรรค์ และบริบทข้ามชาติ-ข้ามพรมแดน, แนวคิดที่เกี่ยวข้องกับปรากฏการณ์ “คติชนสร้างสรรค์” ได้แก่ แนวคิดเรื่อง คติชนแท้-คติชนเทียม (folklore-fakelore), “ของแท้” “ของดั้งเดิม” “วิถีดั้งเดิม” (authenticity), ภาพแทน (representation), ประเพณีประดิษฐ์ (invented tradition), อัตลักษณ์ (identity) ในบทความนี้ได้ยกตัวอย่างวิทยานิพนธ์ในประเทศไทยที่ใช้แนวคิดดังกล่าวข้างต้นมาเป็นกรอบความคิดในการวิเคราะห์ โดยเฉพาะในประเด็นการใช้คติชนในการสร้างอัตลักษณ์ชาติพันธุ์ คติชนประดิษฐ์ในบริบทข้ามพรมแดน ประเพณีประดิษฐ์จากรากฐานทางพุทธศาสนาและประเพณีประดิษฐ์เพื่อการท่องเที่ยวและการพาณิชย์ “Creative Folklore”: A Review of Its Social Context and Related Concepts Siraporn Nathalang Professor, Department of Thai, and Director, Thai Studies Center, Faculty of Arts, Chulalongkorn University, and TRF Senior Research Scholar 2011-2014 Today, culture, particularly folklore, is changing rapidly. However, the pace of change is not intrinsic to culture but is accelerated and determined by social factors. The result is the rise of new forms of and subject matter in folklore. “Creative Folklore: Dynamics and Application of Folklore in Contemporary Thai Society” is a research project aimed at explaining various aspects of the dynamic phenomena of folklore in the context of contemporary Thai society. This article gives a review of social context, related concepts and examples of dissertations concerning the “creative folklore” phenomenon. In this article, the social context related to this phenomenon comprises all these contexts: globalized society and tourism, capitalism and the creative economy, and transnationalism. Its related concepts include folklore-fakelore, “authenticity”, representation, invented tradition and identity. The article reviews dissertations written in Thailand which use these concepts as their analytical framework, especially those focusing on folklore used in expressing ethnic identities, invented folklore in the transnational context, religion-based invented traditions and invented traditions for tourism and commercial purposes.